Isolated tinnitus – premonitory symptom of an evolving auditory dysfunction: a retrospective analysis - Stephen, Marie C. S.; P. N., Bhanuprakash; Venugopalan, Anju; Thimmasettiah, Nagaraj B. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Tinnitus manifests frequently with hearing loss. Isolated tinnitus in patients with self-professed normal hearing may have underlying auditory dysfunction. Methods: We retrospectively reviewed the audiometry record of our department from January 2019 to October 2021. Pure tone audiometry thresholds of patients with isolated tinnitus were analyzed along with the demographics, degree and type of hearing loss. Results: Of 255 (132 males/123 females) patients, mean age 39.7±15.2 years (range: 10-80 years), tinnitus was maximum (49%) prevalent among 20-40 years group, 5.8% among the pediatric population and 8.6% amidst ≥60 years populace. Males predominated (52%) throughout except at 21-30 years age. 83% exhibited some degree of hearing loss (42% bilateral minimal loss, 11% bilateral mild hearing loss). 7% right ears (mostly >50 years age group) and 11% left ears showed greater than mild hearing loss. Bilateral tinnitus presented more (52%) followed by left tinnitus (29%) than right (19%). Mild hearing loss predominated right tinnitus presentation while minimal loss was recorded in left and bilateral tinnitus. However, greater than mild degree of hearing loss was clustered among bilateral tinnitus (14%) followed by left tinnitus (11%) than right tinnitus (6%). 18% had sensorineural deafness and all these patients had bilateral tinnitus. 30% had high frequency hearing loss and 39% among these had 4 kHz dip. Conclusions: Isolated tinnitus may be a premonitory symptom of an underlying or an evolving auditory dysfunction. Bilateral tinnitus followed by left tinnitus presentation warrant higher index of suspicion.